Effect of SB Addition on Mechanical, Electronic and Thermodynamic Properties of Intermetallic B2-Nial: First Principles Study - Bouchentouf Mohamed Amine; Abdiche Ahmed; Ghaffor Djamel; Mokadem Azzeddine; Beloufa Nabil; Bekheira Samir (Annals of West University of Timisoara: Physics)
This study investigates the mechanical, electronic, and thermodynamic properties of B2 NiAl alloyed with Sb, ranging from 0% to 100%. The calculations were conducted using the WIEN2k code based on the full potential linearized augmented plane wave (FP-LAPW) method within the density functional theory (DFT) framework. Generalized Gradient Approximation (GGA) was employed to approximate the exchange-correlation energy. Our analysis of formation enthalpy indicates a preference for Sb to substitute Al sites. Furthermore, we have observed that the mechanical properties of NiAl can be enhanced by adjusting the chemical composition of Sb. Specifically, an increase in antimony content from 0% to 75% results in a notable improvement in ductility tensile, elevating it from 1.92 to 10.72. Conversely, this alteration diminishes the material's strength.